2016
DOI: 10.1001/jamaoto.2016.1809
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the National Surgical Quality Improvement Program Risk Calculator to Predict Complications Following Total Laryngectomy

Abstract: IMPORTANCEThe accuracy of the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) risk calculator has been assessed in multiple surgical subspecialties; however, there have been no publications doing the same in the head and neck surgery literature.OBJECTIVE To evaluate the accuracy of the calculator's predictions in a single institution's total laryngectomy (TL) population. DESIGN, SETTING, AND PARTICIPANTSTotal laryngectomies performed between 2013 and 2014 at a tertiary referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 10 publications
(12 reference statements)
0
26
0
Order By: Relevance
“…[ 11 ] Szender et al [ 7 ] reported limitations of the ACS-NSQIP in evaluating complications in patients in gynecologic oncology. Moreover, the ACS-NSQIP model did not have utility in predicting complications of knee and hip arthroplasties, [ 12 ] total laryngectomy, [ 13 ] and soft-tissue sarcoma resection. [ 14 ] These data, together with our results, suggest the limited value of the ACS-NSQIP risk calculator across patients undergoing different surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Szender et al [ 7 ] reported limitations of the ACS-NSQIP in evaluating complications in patients in gynecologic oncology. Moreover, the ACS-NSQIP model did not have utility in predicting complications of knee and hip arthroplasties, [ 12 ] total laryngectomy, [ 13 ] and soft-tissue sarcoma resection. [ 14 ] These data, together with our results, suggest the limited value of the ACS-NSQIP risk calculator across patients undergoing different surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…in conjunction with a surgery-specific Current Procedure Terminology (CPT) code, to predict patients’ risk of 12 postoperative outcomes within 30 days after surgery [ 12 , 13 ]. Patient-specific variables chosen for the risk calculator are broadly applicable for patients undergoing one of the 1887 procedures covered [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this system has been evaluated in several surgical subspecialties including head and neck surgery [ 8 , 15 – 17 ], urology [ 9 ], neurology [ 10 ], pulmonology [ 18 ], gynecology [ 19 ], gastroenterology [ 12 , 20 23 ], orthopedics [ 24 ] and general surgery with variable results. Despite these numerous publications, very few studies have examined the risk calculator’s efficacy in a Canadian setting [ 13 , 14 ] and none, so far, have evaluated head and neck surgery in a Canadian setting. We aim to provide the first comprehensive evaluation of the risk calculator for head and neck surgery in a Canadian setting by assessing its accuracy in predicting complications following six major head and neck procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the ACS NSQIP SRC has been evaluated in subspecialties with promising results . Few studies have focused on application of this system to head and neck surgery; in general, these studies concluded that the SRC was not a useful tool in predicting postoperative complications in patients undergoing complex head and neck surgeries . However, these studies focus on a widely heterogeneous group of procedures within the scope of head and neck surgery, making it difficult to come to a conclusion about specific procedures.…”
Section: Introductionmentioning
confidence: 99%
“…9 Few studies have focused on application of this system to head and neck surgery; in general, these studies concluded that the SRC was not a useful tool in predicting postoperative complications in patients undergoing complex head and neck surgeries. [10][11][12][13] However, these studies focus on a widely heterogeneous group of procedures within the scope of head and neck surgery, making it difficult to come to a conclusion about specific procedures. The purpose of our study is to assess the validity of the ACS NSQIP surgical risk calculator in predicting postoperative complications in patients undergoing microvascular head and neck reconstruction.…”
Section: Introductionmentioning
confidence: 99%